Towards actionable recommendations for exam preparation using isomorphic problem banks and Explainable Machine Learning - Liu, Chang; Xie, Rui; Chen, Zhongzhou (Frontiers in Education, 2025)
IntroductionMany studies have demonstrated that Machine Learning algorithms can predict students’ exam outcomes based on a variety of student data. Yet it remains a challenge to provide students with actionable learning recommendations based on the predictive model outcome.MethodsThis study examined whether actionable recommendations could be achieved by synchronous innovations in both pedagogy and analysis methods. On the pedagogy side, one exam problem was selected from a large bank of 44 isomorphic problems that was open to students for practice 1 week ahead of the exam. This ensures near-perfect alignment between learning resources and assessment items. On the algorithm side, we compare three Machine Learning models to predict student outcomes on the individual exam problems and a similar transfer problem, and identify important features.ResultsOur results show that 1. The best ML model can predict single exam problem outcomes with >70% accuracy, using learning features from the practice problem bank. 2. Model performance is highly sensitive to the level of alignment between practice and assessment materials. 3. Actionable learning recommendations can be straightforwardly generated from the most important features. 4. The problem bank-based assessment mechanism did not encourage rote learning and exam outcomes are independent of which problems students had practiced on before the exam.DiscussionThe results demonstrated the potential for building a system that could provide data driven recommendations for student learning, and has implications for building future intelligent learning environments.